Critical physician behaviors in the formation of a good physician-patient relationship: Concept mapping the perspective of patients with chronic conditions. Issue 1 (January 2022) - Eigeland, Jessica A.; Jones, Liz; Sheeran, Nicola; Moffitt, Robyn L.
Highlights: A patient-derived conceptual framework for the physician-patient relationship was developed. Critical categories of physician behaviors for forming the physician-patient relationship were elicited from patients. These behaviors are presented in specific, observable and concrete ways to aid physicians in utilizing these skills. Both the framework and the behaviors which constitute the physician-patient relationship extend current models. A change may be required in how the physician-patient relationship is understood in chronic condition care. Abstract: Objective: A robust physician-patient relationship has been linked to better health outcomes for a range of chronic conditions. Our study aimed to identify physician behaviors patients consider contribute to good physician-patient relationships. Method: Fifty patients with a chronic condition and a self-reported good physician-patient relationship were interviewed using the Critical Incidents technique and asked to describe observable behaviors that contributed to their good physician-patient relationship. A sub-sample of 30 participants rated the importance of each behavior and sorted them into self-labelled, mutually exclusive, and conceptually homogenous categories. Multivariate concept mapping with hierarchal cluster analysis was performed. Results: Patients reported 65 behaviors, which were grouped into six overarching domains: valuing the whole person, investigation and future planning, collaboration and empowerment, validation and emotional support, politeness and courtesy, and professionalism. Conclusion: Results indicate patients with chronic conditions have a broader conceptualization and identified additional behaviors that reflect components of the physician-patient relationship than has been identified in researcher and practitioner based models. Practice implications: Practitioners could utilize these concrete behaviors when forming relationships with their patients. These behaviors could also be incorporated into a tool designed to teach and assess the physician-patient relationship.